The consequences of mitochondrial amyloid beta-peptide in Alzheimer's disease. - Muirhead, K; Borger, E; Aitken, L; Conway, S; Gunn-Moore, F (2010)
The Abeta (amyloid-beta peptide) has long been associated with Alzheimer's disease, originally in the form of extracellular plaques. However, in the present paper we review the growing evidence for the role of soluble intracellular Abeta in the disease progression, with particular reference to Abeta found within the mitochondria. Once inside the cell, Abeta is able to interact with a number of targets, including the mitochondrial proteins ABAD (amyloid-binding alcohol dehydrogenase) and CypD (cyclophilin D), which is a component of the mitochondrial permeability transition pore. Interference with the normal functions of these proteins results in disruption of cell homoeostasis and ultimately cell death. The present review explores the possible mechanisms by which cell death occurs, considering the evidence presented on a molecular, cellular and in vivo level.